2016
DOI: 10.3389/fphar.2016.00136
|View full text |Cite
|
Sign up to set email alerts
|

Bioabsorbable Bypass Grafts Biofunctionalised with RGD Have Enhanced Biophysical Properties and Endothelialisation Tested In vivo

Abstract: Small diameter arterial bypass grafts are considered as unmet clinical need since the current grafts have poor patency of 25% within 5 years. We have developed a 3D scaffold manufactured from natural and synthetic biodegradable polymers, poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) and poly(𝜀-caprolactone) (PCL), respectively. Further to improve the biophysical properties as well as endothelialisation, the grafts were covalently conjugated with arginine-glycine-aspartic acid (RGD) bioactive peptides. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 27 publications
2
22
0
1
Order By: Relevance
“…We previously found that either conjugation with RGD peptides or incorporation of VEGF improve biophysical properties of electrospun PHBV/PCL small-diameter vascular grafts [22,23]. Modification with VEGF reduced mean pore area and mean fiber diameter in comparison with modification with RGD peptides [22,23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously found that either conjugation with RGD peptides or incorporation of VEGF improve biophysical properties of electrospun PHBV/PCL small-diameter vascular grafts [22,23]. Modification with VEGF reduced mean pore area and mean fiber diameter in comparison with modification with RGD peptides [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Modification with VEGF reduced mean pore area and mean fiber diameter in comparison with modification with RGD peptides [22,23]. Grafts with incorporated VEGF consisted mostly of nanofibers; on the contrary, those with RGD were formed mostly of microfibers [22,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…And due to this fact the qualityprice ratio of most tissue engineering products are likely to exceed the threshold of availability. However, some developments have been started, and it is hoped that with time researchers will overcome the difficulties [112,113].…”
Section: Resultsmentioning
confidence: 99%
“…Ранее мы показали успешность конъюгирова-ния RGD-пептидов с поверхностью графтов на основе поликапролактона (poly(ɛ-caprolactone), PCL) через карбодиимид, который известен как метод химического перекрестного связывания нулевой длины [5]. Кроме того, в эксперименте in vitro доказано положительное влияние RGD-мо-дификации на клеточную интеграцию [6].…”
unclassified